Tìm x :
3 . 2^x - 3 = 45
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
45 - 3 x (x+2) = 8 x 3 = 24
3 x (x+2) = 45 - 24 = 21
x+2 = 21 : 3 = 7
x = 7-2 = 5
k mk nha
3 x (x+2) = 45 - 24 = 21
x+2 = 21 : 3 = 7
x = 7-2 = 5
chúc bn hok tốt @_@
3*2^x-3=45
3*2^x=45+3=48
2^x=48:3=16
2^x=2^4
=> x=4
Vậy x=4
3.2x-3=45
\(\Rightarrow\)3.2x=45+3
\(\Rightarrow\)3.2x=48
\(\Rightarrow\)2x=48:3
\(\Rightarrow\)2x=16
\(\Rightarrow\)2x=24
\(\Rightarrow\)x=4
-45 : 5 (-3-2x)=3
<=> -9(-3-2x)=3
<=>-3-2x=-1/3
<=> 2x = -8/3
<=> x = -4/3
Vậy ...
\(a,12\left(x-1\right)=0\\ x-1=0\\ x=1\\ b,45+5\left(x-3\right)=70\\ 5\left(x-3\right)=25\\ x-3=5\\ x=8\\ c,3.x-18:2=12\\ 3.x-9=12\\ 3.x=21\\ x=7\)
45- / x+2 / = 27
/ x+2 / = 45-27
/ x+2 / = 18
Suy ra x+2 = 18 hoặc x+2 = -18
Suy ra x =16 x = -20
Vậy x =16 hoặc x = -20
\(5x+\left(1+2+3+4\right)=45\)
\(5x+10=45\)
\(5x=35\)
\(x=7\)
Vậy \(x=7\)
( x + 3 ) + ( x + 5 ) + ( x + 7 ) = 45 x 2
x x 3 + ( 3 + 5 + 7 ) = 90
x x 3 + 15 = 90
x x 3 = 90 - 15
x x 3 = 75
x = 75 : 3
x = 25
\(3.2^x-3=45\)
\(3.2^x=45+3\)
\(3.2^x=48\)
\(2^x=48:3\)
\(2^x=16\)
\(2^x=2^4\)
\(\Rightarrow x=4\)
3 . 2x - 3 = 45
<=> 3 . 2x = 48
<=> 2x = 16
<=> 2x= 24
<=> x = 4(t/m)